Atmospheric Pollutants, Cardiometabolic Disorders, and Dementia in Trajectory Analysis: A 13‐Year Longitudinal Cohort Study - Dong Chen; Yu Long; Yudiyang Ma; Weihong Sha; Lijun Zhang; Yuying Ma; Qinming Li; Jing Feng; Ruijie Zeng; Dongling Luo; Wentao Huang; Yanjun Wu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background First cardiometabolic disorders (FCMDs) and dementia pose a significant burden on aging populations. Investigating the association between atmospheric pollutants and the progression of FCMDs and dementia is crucial. Methods A prospective analysis was conducted on 413 149 participants from the UK Biobank. Atmospheric pollutant concentrations were calculated using land‐use regression models. We used a multistate model and calculated the polygenic risk score for dementia to analyze the associations of pollutants on the relevant trajectories from baseline to FCMD, subsequent dementia, and death. Results Over 13 years, 65 336 patients with FCMD were identified, with 2584 developing dementia and 10 664 dying. Each interquartile range increase in pollutant concentrations showed the hazard ratios (HRs) of particulate matter with aerodynamic diameter ≤2.5 μm (HR, 1.03 [95% CI, 1.02–1.05]); nitrogen dioxide (HR, 1.04 [95% CI, 1.03–1.05]), and nitrogen oxides (HR, 1.03 [95% CI, 1.02–1.04]) for transitioning from baseline to FCMD; particulate matter with aerodynamic diameter ≤2.5 μm (HR, 1.11 [95% CI, 1.05–1.16]; nitrogen dioxide: HR, 1.12 [95% CI, 1.06–1.18]; and nitrogen oxides (HR, 1.07 [95% CI, 1.03–1.12]) for transitioning from FCMD to dementia, and the association between pollutants and this trajectory remained consistent after adjusting for genetic susceptibility to dementia (particulate matter with aerodynamic diameter ≤2.5 μm: HR, 1.06 [95% CI, 1.04–1.08]; nitrogen dioxide: HR, 1.05 ([95% CI, 1.03–1.07); and nitrogen oxides: HR, 1.05 [95% CI, 1.03–1.06]) for transitioning from baseline to death; and particulate matter with aerodynamic diameter ≤2.5 μm: HR, 1.03 ([95% CI, 1.00–1.05); nitrogen dioxide: HR, 1.05 ([95% CI, 1.02–1.08); nitrogen oxides: HR, 1.04 ([95% CI, 1.01–1.06]) for transitioning from subsequent FCMD to death. Particulate matter with aerodynamic diameter ≤10 μm was only significantly associated with the transition from baseline to FCMD. Conclusions Our study provides the first evidence that atmospheric pollutants are associated with the progression of FCMD and subsequent dementia.